Pemanfaatan Limbah Onggok Aren dan Ampas Tebu sebagai Inovasi Batako Ramah Lingkungan - Aisyah Rindi Antika; Hilda Ari Ashara; Bambang Setiabudi; Hartono H (Jurnal Sipil dan Arsitektur, 2023)
Brick is a wall building material that is currently widely chosen because it is considered more efficient in terms of installation. This research utilizes solid waste in the form of sugar palm husks and sugar cane bagasse as an environmentally friendly brick innovation. The method used in this research is the experimental method. The parameters to be achieved in this research are the compressive strength and water absorption values regulated in SNI 03-0349-1989. The percentage of bagasse ash that will be added is 0%, 2.5%, 5%, 7.5% and 10% of the weight of cement and palm sugar palm fruit is 1% of the weight of sand using FAS (Cement Water Factor) of 0.35 . The average compressive strength and water absorption values produced were 10.52 Mpa and 5.4%, 15.76 Mpa and 4.9%, 17.62 Mpa and 4.6%, 23.65 Mpa and 4.5 %, and 5.14 Mpa and 7.9%. The use of these two materials can increase the compressive strength of bricks optimally at a percentage of bagasse ash of 7.5% and palm sugar palm 1%. This innovation can reduce waste and become a brick business opportunity for local communities at lower costs.